Analisis Bangkitan Perjalanan Dari Perumahan Griya Aster Kecamatan Legok Kabupaten Tangerang - Fajrinia, Citto Pacama; Upa, Verdy Ananda; Putra, Dhiaz Mulyana (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of Griya Aster Residence without considering transportation aspects has led to issues such as traffic congestion in the Legok area. The road access in Griya Aster Residence was designed without considering trip generation calculations. This studyaims to determine trip generation model, calculate the total of trip generation, and analyze the factors effecting trip generation in Griya Aster Residence, Legok, Tangerang Municipal. The research method used was a household interview regarding the number of family members, monthly income, number of working individuals, number of school-age individuals, vehicle ownership, monthly transportation cost, and daily trips made by each family member. The collected data were then analyzed using multiple linear regression method used SPSS 25.0 software with significant level 95%. The trip generation model obtained for Griya Aster Residence is Y = -0,327 + 0,514 X1 + 0,398 X3 + 0,012 X4 + 0,580 X5 with R2 (R square) = 0,618. The total trip generation for Griya Aster Residence is 763 trips/day, based on the t-Test with a significant value of <0,05, the factors influencing trip generation in Griya Aser Residence includes the number of family members, monthly income, number of working individuals, number of school-age individuals, vehicle ownership, and monthly transportation costs.